CAR T-Cell Therapy for Cancer: Latest Updates and Challenges, with a Focus on B-Lymphoid Malignancies and Selected Solid Tumours - Hiu Kwan Carolyn Tang; Bo Wang; Hui Xian Tan; Muhammad Adeel Sarwar; Bahaaeldin Baraka; Tahir Shafiq; Ankit R. Rao (Cells, 2023)
Although exponential progress in treating advanced malignancy has been made in the modern era with immune checkpoint blockade, survival outcomes remain suboptimal. Cellular immunotherapy, such as chimeric antigen receptor T cells, has the potential to improve this. CAR T cells combine the antigen specificity of a monoclonal antibody with the cytotoxic ‘power’ of T-lymphocytes through expression of a transgene encoding the scFv domain, CD3 activation molecule, and co-stimulatory domains. Although, very rarely, fatal cytokine-release syndrome may occur, CAR T-cell therapy gives patients with refractory CD19-positive B-lymphoid malignancies an important further therapeutic option. However, low-level expression of epithelial tumour-associated-antigens on non-malignant cells makes the application of CAR T-cell technology to common solid cancers challenging, as does the potentially limited ability of CAR T cells to traffic outside the blood/lymphoid microenvironment into metastatic lesions. Despite this, in advanced neuroblastoma refractory to standard therapy, 60% long-term overall survival and an objective response in 63% was achieved with anti GD2-specific CAR T cells.